THE IMPACT OF RELIGIOSITY AND USER PERCEPTIONS ON MOBILE PAYMENT ADOPTION AMONG STUDENTS AT ISLAMIC UNIVERSITIES IN YOGYAKARTA - Virgiawan, Rheyza; Aditya, Achmad; Mohamad, Rosyad Denhas (Universitas Muria Kudus, 2024)
This study aims to analyze the influence of religiosity on university students' interest in using mobile payment services through the extended Technology Acceptance Model (TAM). The research objective is to examine how perceived usefulness (PU), perceived ease of use (PEU), perceived security (PS), and religiosity (R) impact mobile payment adoption among students in Islamic universities in Yogyakarta. Data was collected from January to March 2024 via a Google Form questionnaire involving 203 students from Islamic universities in Yogyakarta. The quantitative analysis was performed using Smart-PLS. The findings indicate that among the four exogenous variables, only perceived usefulness (PU) significantly and positively affects mobile payment adoption, highlighting its crucial role in influencing student adoption decisions. Conversely, perceived ease of use (PEU), perceived security (PS), and religiosity (R) showed positive but insignificant effects on mobile payment adoption. Limitations include the relatively small sample size and the focus on a specific demographic, which may affect the generalizability of the results. Future research should explore a larger and more diverse population, include additional variables such as cultural and socioeconomic factors, and employ longitudinal studies to better understand the dynamics of mobile payment adoption over time.